Bioconversion of organic solid wastes by black soldier fly larvae - Tay, See Yee (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
Nowadays, the utilization of black soldier fly larvae (BSFL) in bioconversion is getting popular as it capable of degrading waste efficiently and recover the nutrient of waste. This research was designed to evaluate the capacity of BSFL to biologically convert differenttypes of selected waste. Besides, this project also aimed to assess the BSFL growth rate and to study body protein and fat composition of BSFL with respect to different types of waste. In this project, the result successfully showed that BSFL is capable of digesting a wide range of waste which including goat manure, banana and cabbage but differ in the decomposition rate. In addition, the study showed that the waste reduction capacity was ranged from 21.82-36.74% which the highest was achieved by banana and the lowest was goat manure. Next, the highest growth rate of BSFL which in term of weight, diameter and length were achieved cabbage and then followed by banana, while lowest was recorded by goat manure. Lastly, the protein content of BSFL was achieved in the range of 27.61-40.34% while the lipid content of BSFL was recorded in range of 11.00-53.33%. This study has identified two important factors that strongly influenced waste reduction capacity and growth rate as well as BSFL nutritional content: (1) moisture content and (2) nutritional content of the diet.